2012
DOI: 10.4103/0970-9185.101903
|View full text |Cite
|
Sign up to set email alerts
|

A randomized double-blind placebo-controlled clinical study on the effects of gabapentin premedication on hemodynamic stability during laparoscopic cholecystectomy

Abstract: Background:Carbon dioxide pneumoperitoneum for laparoscopic surgery increases arterial pressures, heart rate, and systemic vascular resistance. In this randomized double-blind placebo-controlled clinical study, we investigated the efficacy of gabapentin premedication to provide perioperative hemodynamic stability in patients undergoing laparoscopic cholecystectomy.Materials and Methods:Sixty patients, of either sex (18–65 years of age) undergoing elective laparoscopic cholecystectomy were randomly allocated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 20 publications
3
20
0
Order By: Relevance
“…while Myung et al found that in rats intrathecal and intraperitoneal gabapentin did not induce significant changes of hemodynamics over the 60 min compared to the baseline value [20]. Mausumi et al found that gabapentin provide hemodynamic stability during laparoscopic surgery in both sexes and this compatible with our study [21].…”
Section: Discussionsupporting
confidence: 81%
“…while Myung et al found that in rats intrathecal and intraperitoneal gabapentin did not induce significant changes of hemodynamics over the 60 min compared to the baseline value [20]. Mausumi et al found that gabapentin provide hemodynamic stability during laparoscopic surgery in both sexes and this compatible with our study [21].…”
Section: Discussionsupporting
confidence: 81%
“…A total of 135 studies were included . One hundred and thirty‐two trials with 9498 patients were included for the evaluation of benefit and furthermore, three non‐randomized studies were included for the evaluation of harm.…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen trials had overall low risk of bias . Seventy‐seven trials had high and 39 trials unclear risk of bias . Reasons for unclear and high risk of bias were mainly ‘selective outcome reporting’ or ‘other bias’ (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4] Pharmacological agents like β-blockers, opioids, nitroglycerine and dexmedetomidine have been used to minimize such derangements with varied results. [5][6][7][8][9] Nitroglycerine (NTG) is commonly used as a rescue measure for intraoperative hypertension. 10,11 Clonidine, an -2 adrenoreceptor agonist, reduces sympathetic outflow and is advantageous in laparoscopic procedures.…”
Section: Introductionmentioning
confidence: 99%